The holism principle in agriculture sustainable development - Józef Stanisław Zegar; Wioletta Wrzaszcz (Economic and Environmental Studies (E&ES), 2017)
The idea of sustainable development, extended at the end of 20th century, takes the form of a strategic concept in the field of socio-economic development in many countries and their regional groupings. It is also being promoted by international organizations, considering the United Nations and NGOs. The concept usually involves three aspects, namely environmental, economic and social, in formulating corresponding goals and ways of achieving them. The implementation of this concept is a huge challenge due to the nature of market mechanism. This concept also applies to agriculture, which is a complex system. Sustainable agriculture should be considered at the different levels of vertical order - in particular at the level of agricultural holdings (microeconomic level), state (macroeconomic level) and global (planetary level). The order determines the hierarchy of objectives for agriculture sustainable development and measures to achieve them. Economic objectives are the most important in the case of farms, while social goals should dominate at the state level. At the global level, environmental objectives are particularly significant, because of biosphere natural limits. Defining socially rational solutions require holistic approach to agriculture sustainable development. This applies both horizontal analysis (different aspects, different purposes, different activities), as well as vertical considerations (taking into account microeconomic, macroeconomic and planetary level). The aim of paper is to present the significance of the holistic approach in the implementation of sustainable development principles at different agriculture levels - farm, sector, global.
Keywords: Q01; Q10; Q12; Q13; Q56; 330; the holism principle; agriculture sustainable development; agricultural holdings; microeconomic; macroeconomic and planetary level